FRI0371 Characteristics of gout patients in france: The "cactus" study. (23rd January 2014) - Flipo, R.-M.; Errieau, G.; Perrissin, L.; Richette, P.
Abstract : Background: There was little recent information in France concerning gout patients despite data from other countries supporting increasing disease prevalence due to dietary and lifestyle changes, and increased longevity of populations. Objectives: The primary objective of the French CACTUS study was to describe in real-life conditions the characteristics and serum uric acid (sUA) concentrations in gout patients. Methods: CACTUS was a non interventional transversal and multicenter study conducted in routine practice. From November 2010 to May 2011, 2812 gout patients were consecutively included by 857 general practitioners and 92 rheumatologists. Descriptive analyses were performed according to patients' sUA levels. Results: A total of 2444 patients having recent sUA data (<1 year) were analysed (mean age 64±12 years; men 83%). Their median gout duration was 3.5 years [0.1 – 50.0] with a mean sUA concentration of 8.5±1.2 mg/dL at first diagnosis. Overall, 89% of patients had primary gout and 23% a family history of gout. Their most frequent risk factors and comorbidities were hypertension (66%), hyperlipidemia (59%), obesity (47%) and diabetes (23%). 71% of patients had a metabolic syndrome according to the International Diabetes Federation definition, and 24% were current smokers. Alcohol (>30g/day) and beer (≥1 glass/day) consumption was observed in 47% and 27% of cases respectively, whereas 11% of patients consumed sweetened soft drinks (≥1 serving a day) only. Among symptoms of gout, tophi were reported in 11% of patients. During the previous year, patients had 2±2 gout attacks in mean and 7% presented renal colic. Their mean last uric acid concentration (<1 year) was 7.4±1.7 mg/dL, 8.3±1.4 mg/dl in patients diagnosed with gout the day of the study visit (n=115), 7.2±1.7 mg/dL in patients already treated at inclusion (n=2003), and 7.9±1.4 mg/dL in non-treated patients (n=326). An analysis focused on the subgroup of patients (n=1689) with a gout diagnosis before inclusion, previously using at least one uric acid-lowering therapy and still receiving one treatment at inclusion, showed a mean sUA concentration of 7.1±1.7 mg/dL; only 24% of them achieved a sUA level of ≤6 mg/dL (]6; 7[ mg/dL: 18%, [7; 9[ mg/dL: 46%, ≥9 mg/dL: 12%). Patients achieving the <6mg/dl objective, significantly differed from the others regarding their alcohol (52% vs. 41%, p<0.001) or sweetened soft drinks consumption (11% vs. 8%, p<0.028); they had also a greater waist circumference than patients who achieved the sUA target (men ≥94 cm or women ≥80 cm: 84% vs. 79%, p<0.020). Conclusions: This study provides updated data on a large population of French patients suffering from gout. Main finding was the relatively low proportion of treated patients who achieved a sUA level ≤6 mg/dL. These results suggest that there is a need for improved efforts to provide adequate control of hyperuricemia in treated patients with chronic gout including pharmacological, non-pharmacological and global approaches (weight loss, dietary changes, and adequate management of combined aging-related diseases). Disclosure of Interest: R.-M. Flipo Grant/Research support from: has received honoraria from Menarini, G. ERRIEAU Grant/Research support from: has received honoraria from Menarini, L. PERRISSIN Employee of: of the sponsor, P. RICHETTE Grant/Research support from: has received honoraria from Menarini